Political Geography and the Region in Indian History : Daksina Kosala and Vidarbha, c. 400-1300 CE - Kumar, Kundan, (Brill | Manohar Publishers & Distributors, 2024)
This epigraphic study of the political geography of two historical regions, Dakṣiṇa Kośala and Vidarbha between fourth and thirteenth centuries, focuses on the interaction of physical and human geography as reflected in the changing nature of settlement patterns both rural and urban and their political organization through time - an important exercise, based primarily on Sanskrit inscriptions from the period and the region. The study contributes to further substantiation of the critical significance of the conception of early medieval in the study of Indian history. Since almost all the inscriptions are in the nature of land grants to Brahamans, shrines and monasteries, a related area of investigation is the extent of agrarian expansion in the context of political and administrative changes initiated by a series of dynasties across centuries. This also involved a gradual growth of a sense of affiliation with the region or conscious effort to appropriate its identity by the ruling dynasties. The book critically analyses the data meticulously presented in tabulated form - an established method in inscription-based studies of early medieval India. It thus adds to our knowledge and understanding of the region as it has gradually evolved over several centuries through the early medieval period.